ChemInform Abstract: Highly Diastereoselective Synthesis of Methylenecyclobutanes by Merging Boron‐Homologation and Boron‐Allylation Strategies. Issue 17 (April 2016) - Eisold, Michael; Didier, Dorian
Abstract: The uncatalyzed reaction of cyclobutenylmethyl boron compounds (I) and (IV) with aldehydes results in the efficient formation of methylene cyclobutanes (III) and (V).